2017
DOI: 10.1007/s10620-017-4684-x
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Nonalcoholic Steatohepatitis in the US: Temporal Trends and Outcomes

Abstract: Currently, NASH is the most rapidly growing indication for LT in the US. Despite resurgence in ALD, NASH remains the second leading indication for LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
160
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(170 citation statements)
references
References 23 publications
4
160
2
4
Order By: Relevance
“…In contrast, the demand for LT for hepatitis C virus (HCV) has declined since 2015 following the introduction of safe and effective direct‐acting antivirals. Consequently, current trends suggest that NASH will surpass HCV as the most common indication for LT in the United States within the next 10 years …”
mentioning
confidence: 99%
“…In contrast, the demand for LT for hepatitis C virus (HCV) has declined since 2015 following the introduction of safe and effective direct‐acting antivirals. Consequently, current trends suggest that NASH will surpass HCV as the most common indication for LT in the United States within the next 10 years …”
mentioning
confidence: 99%
“…The outcomes of LT for NASH were similar to those of LT performed for ALD. Patients with NASH who underwent LT experienced superior outcomes compared to those reported for LT of HCV recipients in the USA [3]. There are reasons to believe that future studies may yield results different than those reported for LTs performed from 2003 to 2014.…”
mentioning
confidence: 83%
“…In this issue of Digestive Diseases and Sciences, Cholankeril et al [3] report on the temporal trends and outcomes of LT for NASH in the USA based on a review of the United Network for Organ Sharing and Organ Procurement and Cholankeril et al have reclassified from CC to NASH the cases of all obese patients (BMI C 30 kg/m 2 ) that underwent LT for CC [3]. This measure was clearly justified, as it is now accepted that the majority of CC patients actually have undiagnosed NASH [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Later stages are NASH, with the risk of progressing to liver cirrhosis including the so‐called “cryptogenic” cirrhosis, which is still debatable, and eventually hepatocellular carcinoma (HCC) . A liver transplantation may be the therapy of choice . Defining various stages of obesity‐related liver diseases requires a liver histology, considered the gold standard, obtained by invasive liver biopsy .…”
Section: Nafld and Nashmentioning
confidence: 99%